2010
DOI: 10.1002/ajmg.a.33133
|View full text |Cite
|
Sign up to set email alerts
|

PAX2 mutations in fetal renal hypodysplasia

Abstract: Papillorenal syndrome also known as renal-coloboma syndrome (OMIM 120330) is an autosomal dominant condition comprising optic nerve anomaly and renal oligomeganephronic hypoplasia. This reduced number of nephron generations with compensatory glomerular hypertrophy leads towards chronic insufficiency with renal failure. We report on two fetuses with PAX2 mutations presenting at 24 and 18 weeks' gestation, respectively, born into two different sibships. In our first patient, termination of pregnancy was elected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
(35 reference statements)
0
29
0
1
Order By: Relevance
“…These genes were chosen, because (1) they are routinely screened in our laboratory, (2) they have been shown to also be involved in patients with CAKUT without extrarenal anomalies (5,(13)(14)(15), and (3) PAX2 was recently shown to be involved in one case of severe prenatal CAKUT (17). Thirty-one fetuses had been previously screened for RET mutations in another study (11).…”
Section: Discussionmentioning
confidence: 99%
“…These genes were chosen, because (1) they are routinely screened in our laboratory, (2) they have been shown to also be involved in patients with CAKUT without extrarenal anomalies (5,(13)(14)(15), and (3) PAX2 was recently shown to be involved in one case of severe prenatal CAKUT (17). Thirty-one fetuses had been previously screened for RET mutations in another study (11).…”
Section: Discussionmentioning
confidence: 99%
“…Seven fetuses had severe prenatal renal failure with confirmation of the presence of a PAX2 mutation [Martinovic-Bouriel et al, 2010;Supp. Table S1, Families 31, 55, 71, and 82].…”
Section: Fetal Potter Sequencementioning
confidence: 94%
“…A review of four case series revealed that 13/148 (∼9%) of individuals tested due to a primary diagnosis of renal hypoplasia had mutations in the PAX2 gene [Martinovic-Bouriel et al, 2010;Nishimoto et al, 2001;Salomon et al, 2001;Weber et al, 2006]. Of the 13 mutation-positive individuals, further ophthalmological evaluation revealed optic nerve abnormalities in 10 individuals, while three mutation-positive individuals reportedly had a normal ophthalmological exam.…”
Section: Isolated Renal Hypodysplasiamentioning
confidence: 99%
“…ESRD may present prenatally with severely hypoplastic or aplastic kidneys and oligohydramnios resulting in fetal loss. 18,27 ESRD has been identified shortly after birth 3,18 and can occur as late as the seventh decade. 12,18 A single case of a surviving infant with Potter sequence, optic nerve malformations and a PAX2 mutation has been reported.…”
Section: Renal Findingsmentioning
confidence: 99%